The potential combination of smart and active packaging in one packaging system in improving and maintaining the quality of fish - Dewi Sisilia Yolanda; Andi Dirpan; Andi Nur Faidah Rahman; Muspirah Djalal; Serli Hatul Hidayat (Hasanuddin University Food Science and Technology Study Program, 2020)
Fresh food with a long shelf life with little or no preservatives is being a hot issue. In response to the issue, various forms of packaging technology innovation were created, such as smart packaging and active packaging. The packaging innovation in this study was designed to provide quality assurance of packaged food to consumers, especially for Tuna fillets. The purpose of this study was to determine the color change profile of smart indicator labels, to determine the effectiveness of active paper (addition of garlic extract 0%, 5%, 10%, and 15%) when applied to Tuna fillets stored at room temperature (28 ± 2oC), and to find out the level of correlation between smart indicator labels and active paper against various parameters of Tuna fillet rot test like total volatile base nitrogen (TVBN), total bacteria (TPC), and pH. All these parameters were tested at room temperature every 2 hours until 12 hours with two replications. The results obtained showed that the smart label indicator changed color from dark red to yellow when the fillet was decomposed. Active paper with the addition of garlic extract concentration of 15% had the best effectiveness in minimizing the occurrence of any deterioration in the Tuna fillets during storage, which was then followed by a concentration of 10%, 5%, and 0%. The level of correlation between the value of the smart indicator color analysis and the effectiveness of the active paper on various fish rot test parameters showed a positive correlation which showed the same tendency pattern in the detection rate of the decomposition of Tuna fillet.